Development of Arabic Language Learning Media Using the Smart Apps Creator Application to Enhance Language Skills - Ferdiansyah, Novan; Hamid, Mohammad Abdul; Hasan, Nur (Abjadia : International Journal of Education, 2025)
This study aims to develop a listening skill learning application based on Smart Apps Creator for IAIN Madura students. This study uses a Research and Development approach with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. There are two types of data from this study, namely qualitative and quantitative data. Qualitative data is obtained from observation and interviews, while quantitative data is obtained from tests and questionnaires. The researcher's data analysis technique uses the miles and Huberman technique, while the researcher's quantitative data analysis technique uses a Likert scale to determine the feasibility of the application from the validator of media experts, materials, lecturers, and students. And using a paired sample T test to determine the effectiveness of using the application by giving a pretest and post-test, before and after treatment to 7 students during a limited test, and 27 students during a field trial. The results of the application feasibility questionnaire obtained a score of 93% from media experts, and 96% from material experts, and 89% from lecturers, and 89% from students with a very feasible category. Normality test on pretest value 0.115 and post-test 0.392 greater than 0.05 indicates normally distributed data, Homogeneous test obtained 0.207 greater than 0.05 indicates homogeneous variance. Paired sample T test obtained significance value 0.000 less than 0.05, then Ho is rejected and H1 is accepted, indicating that the application of listening smart is effective in learning listening skill for IAIN Madura students.